The impacts on the mental health of residents of 16 favelas observed during the coronavirus pandemic in Brazil (Research, Society and Development, 2021)
The COVID-19 pandemic in Brazil has caused a scenario of extreme social vulnerability, with high unemployment rates and severe cuts to social benefits and policies. Aims: analyze the impacts of the pandemic on the mental health and quality of life on people living in contexts of high-levels of armed and lethal violence and social fragility. Methods: A longitudinal cohort study was undertaken with a convenient sample of fifty individuals who live in 16 favelas in Rio de Janeiro (Brazil) before and during the COVID-19 pandemic. The interviews included enquired about the respondent’s capacity to cope with the pandemic and their access to services as well as questions about mental health (Brief Symptoms Inventory), and Quality of Life (Manchester Short Assessment of Quality of Life). Results: The results revealed a decrease in the somatization dimension of the BSI scale and a worsening on the objective index (SIX) of quality of life. Mental health distress increased more in the male group when compared to the female group during the COVID-19 pandemic. It seems likely; therefore, the COVID-19 pandemic presents a major challenge for people living in a context of urban violence and social deprivation. Conclusions: The worsening of mental distress and quality of life during the pandemic impacts both genders and suggests the need for policies directed to health and employment protection.